Wheels of justice & cycles of abuse: what barriers do victims of domestic violence in South Africa face when seeking the protection of the courts? - Waldman, Jessica (Department of Public Law, 2021)
This dissertation considers the barriers facing victims of domestic violence who seek protection orders under the South African Domestic Violence Act 1998 (DVA). 1 It looks at the key players responsible for implementing the protection order process: clerks, court support workers, magistrates and police, and the challenges posed by the way that they interact as the 'courtroom workgroup.'2 This topic is examined through qualitative empirical research in the Western Cape with court support workers, independent victims' advocates who sit within the courts, advising and assisting applicants, and offering them psychosocial support. Domestic violence victims often present at court seeking a protection order during a time of crisis; some are at risk of their life. 3 Therefore, for many applicants, in order for the protection of the courts to be effective, it should be provided on the day of application. Interim protection orders and interim warrants of arrest are intended to give immediate protection to the applicant. However the way in which the courts and police have implemented their respective obligations under the DVA leads to inconsistency, arbitrariness, unfairness, delay and ultimately a failure to provide protection to vulnerable applicants within an appropriate time period, or at all. Participants suggested that systemic issues including complex forms, long waiting times, overstretched staff, poor communication by the courtroom workgroup with service users, and non-compliance with the DVA by police create significant barriers to applicants. Many applicants are left bewildered or disillusioned and do not complete the protection order process, leaving them without protection. Consequently, under the current system, the courts and police are failing to uphold their human rights obligations towards applicants for protection orders. These are long-standing issues, which have been noted by academics and civil society for 20 years, yet it appears that there has been little improvement. 4 Reform of the DVA should be accompanied by improved training, accountability and victim-centric policy guidance for the courtroom workgroup. As well as widening the scope of the DVA, these should address the deficits in implementation of the current law.